2020
DOI: 10.1002/ps.6085
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in cyp51b and overexpression of cyp51a and cyp51b confer multiple resistant to DMIs fungicide prochloraz in Fusarium fujikuroi

Abstract: BACKGROUND Fusarium fujikuroi is a plant pathogen that causes rice bakanae disease. Prochloraz is an imidazole‐class sterol, 14α‐demethylase inhibitor (DMI), which has been in use for several years as a foliar spray to control Fusarium spp. on agriculturally important monocot crops. F. fujikuroi is highly resistant to prochloraz treatment, and the aim of this study was to clarify the mechanism by which F. fujikuroi renders itself resistant to prochloraz. RESULTS Recently, prochloraz‐resistant strains were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Such cases become more and more widespread [14]. Indeed, Prochloraz-responsive genes facilitating DMI-resistance have already been reported in other phytopathogens (see, for example [15,16]. One solution to cope with this problem is the use of a mixture of fungicides, each of which has a different action mechanism (see, for example [17,18]).…”
Section: Discussionmentioning
confidence: 99%
“…Such cases become more and more widespread [14]. Indeed, Prochloraz-responsive genes facilitating DMI-resistance have already been reported in other phytopathogens (see, for example [15,16]. One solution to cope with this problem is the use of a mixture of fungicides, each of which has a different action mechanism (see, for example [17,18]).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the amino acid site mutation of CYP51A (Y459S/D/N, Y461S/H, I381V) and CYP51B (I381V) in M. graminicola resulted in moderate resistance against DMI fungicides (Leroux et al., 2007). The amino acid mutation of the CYP51B gene (S312T) and overexpression of FfCYP51A and FfCYP51B resulted in the resistance to DMI fungicides in F. fujikuroi (Zhang et al., 2021). A point mutation (Y136F) at the 136th amino acid of CYP51 protein in Erysiphe graminis resulted in resistance of E. graminis to DMI fungicides (Yan et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is required for biosynthesis of ergosterol, a component of the fungal cell membrane that is essential for fungal growth. F. fujikuroi has three CYP51 genes (CYP51A, B, and C) [44]. DMIs include chemical classes such as imidazole, piperazine, pyridine, pyrimidine, and triazole.…”
Section: Sterol Demethylase Inhibitorsmentioning
confidence: 99%
“…Furthermore, in case of another Korean strain CF337, structure changes in the fungal cell wall and an ATP binding cassette (ABC) transporter were reported to confer prochloraz resistance [55]. Whereas, Zhang et al [44] reported that the S312T mutation in CYP51B and overexpression of the CYP51A/CYP51B genes caused prochloraz resistance in Chinese F. fujikuroi. Choi et al [56] found an association between survival factor 1 and F-box/WD-repeat protein with prochloraz sensitivity of F. fujikuroi.…”
Section: Sterol Demethylase Inhibitorsmentioning
confidence: 99%